366PActivity of larotrectinib in TRK fusion cancer patients with primary central nervous system tumours. (24th November 2019) - Ziegler, D S; Doz, F; Geoerger, B; Dubois, S; Grilley-Olson, J E; van Tilburg, C; Italiano, A; Lissat, A; Kang, J-H; Tahara, M; Boni, V; Perreault, S; et al.
Abstract: Background: TRK fusions are oncogenic drivers of a variety of tumors, many of which can involve the central nervous system (CNS). Larotrectinib is an FDA-approved selective TRK inhibitor for the treatment of TRK fusion cancer (Drilon et al., NEJM 2018). Here we report on the clinical activity of larotrectinib in an expanded set of TRK fusion-positive primary CNS tumors. Methods: Patients with primary CNS tumors harboring an NTRK gene fusion detected by local molecular testing who were treated with larotrectinib in two clinical trials (NCT02637687 and NCT02576431) were identified. Larotrectinib was administered until disease progression, withdrawal, or unacceptable toxicity. Disease status was investigator assessed (RANO). Data cutoff: February 19, 2019. Results: 18 patients with various histological types of glial tumors (11 high grade, 4 low grade, 3 unknown) were identified. The patients had gene fusions involving NTRK2 (n = 13), NTRK1 (n = 3) and NTRK3 (n = 2). Median age was 10.5 years (range 1.3–79.0); 14 patients were pediatric (< 18). In 14 evaluable patients, the objective response rate was 36% (2 CR [pending confirmation], 3 PR), with responses seen in high- and low-grade disease and across histologies. Nine patients had SD. The 24-week disease control rate was 71%. The duration of treatment ranged from 0.03+ to 16.6+ months. Conclusions: Larotrectinib is active in patients with TRK fusion cancer with intracranial disease. Objective responses and durable disease control were seen in primary CNS tumors of various grades and histologies. These results further support expanded testing for NTRK gene fusions in patients with primary CNS tumors. Clinical trial identification: NCT02637687 and NCT02576431. Legal entity responsible for the study: Bayer. Funding: Bayer. Disclosure: All authors have declared no conflicts of interest.